Exploring Measurement Model for Entrepreneurial Marketing Construct: A Marketing for SME’s - Sheerad Sahid; Nurul Fadly Habidin (International Journal of Supply Chain Management, 2018)
This paper examined the validity of the entrepreneurial marketing (EM) construct in the context of small and medium enterprises (SME) in Malaysia, which contributes to the marketing and entrepreneurship interface literature. This study conducted self-administered survey among SME owners-managers. Accordingly, this study performed two-stage analysis, which were exploratory factors analysis (sample of 101 respondents in the pilot study) and confirmatory factor analysis (sample of 221 respondents in the field study). Obtained results demonstrated the reliability and validity of the four-dimensional EM construct (opportunity creation, customer intimacy-based innovative product, resource enhancement, and legitimacy) for further analysis. It is recommended to evaluate the effectiveness of the proposed EM construct in enhancing the business performance of SMEs. Essentially, this study empirically examined the EM construct using structural equation modeling approach, which expands the domain of EM.